Figurative and Imagery Language in Poetry set Melihat Api Bekerja by M. Aan Mansyur: Stylistic Review (Universitas Negeri Semarang, 2019)
Poetry is a medium for poets to express or utter their notions and intended purposes to readers. This research objective is to analyze the form, meaning, function of figurative language and image as well as the relationship between figurative language and their correlations in poetry set Melihat Api Bekerja by M. Aan Mansyur. The data were poetry excerpts which had appropriateness to problem sings. The data were gained through literature study and hermeneutic reading. This review of the poetry set used stylistic review. The findings showed: first, there were 76 figurative languages consisting of 27 similes, 17 metaphors, 18 personifications, 3 metonymies, 3 synecdotes, and 8 idioms; second, there were 77 imageries consisting of 41 visual images, 8 audio images, 2 smelling images, 1 tasting image, 19 palpability images, and 6 movement images; third, there were 6 correlations of figurative and imagery language. A significant founding in this research is a poetry collection Melihat Api Bekerja by M.Aan Mansyur can increase reader interest in figurative language and imagery comprehension. the benefits of these research for the readers to get and understand figurative language and imagery in poetry collection Melihat Api Bekerja by M.Aan Mansyur.